The perceptions of female youth regarding Menstrual Hygiene Management (MHM) in Roodeplaat, Tshwane - Carbonatto, C L (University of Pretoria, 2022)
Mini Dissertation (MSW (Healthcare))--University of Pretoria, 2022.